Neglected tropical diseases of the Middle East and North Africa: review of their prevalence, distribution, and opportunities for control. - Peter J Hotez; Lorenzo Savioli; Alan Fenwick (Public Library of Science (PLoS), 2012)
The neglected tropical diseases (NTDs) are highly endemic but patchily distributed among the 20 countries and almost 400 million people of the Middle East and North Africa (MENA) region, and disproportionately affect an estimated 65 million people living on less than US$2 per day. Egypt has the largest number of people living in poverty of any MENA nation, while Yemen has the highest prevalence of people living in poverty. These two nations stand out for having suffered the highest rates of many NTDs, including the soil-transmitted nematode infections, filarial infections, schistosomiasis, fascioliasis, leprosy, and trachoma, although they should be recognized for recent measures aimed at NTD control. Leishmaniasis, especially cutaneous leishmaniasis, is endemic in Syria, Iran, Iraq, Libya, Morocco, and elsewhere in the region. Both zoonotic (Leishmania major) and anthroponotic (Leishmania tropica) forms are endemic in MENA in rural arid regions and urban regions, respectively. Other endemic zoonotic NTDs include cystic echinococcosis, fascioliasis, and brucellosis. Dengue is endemic in Saudi Arabia, where Rift Valley fever and Alkhurma hemorrhagic fever have also emerged. Great strides have been made towards elimination of several endemic NTDs, including lymphatic filariasis in Egypt and Yemen; schistosomiasis in Iran, Morocco, and Oman; and trachoma in Morocco, Algeria, Iran, Libya, Oman, Saudi Arabia, Tunisia, and the United Arab Emirates. A particularly noteworthy achievement is the long battle waged against schistosomiasis in Egypt, where prevalence has been brought down by regular praziquantel treatment. Conflict and human and animal migrations are key social determinants in preventing the control or elimination of NTDs in the MENA, while local political will, strengthened international and intersectoral cooperative efforts for surveillance, mass drug administration, and vaccination are essential for elimination.